Establishment of a thermal process for binagol in glass jars - Jimenez, Maud Ariane Grefiel
ABSTRACT Formulation of binagol was chosen from among the different manufacturers in Dagami, Leyte. The pH and aw, which are significant processing characteristics of the cooked binagol were determined to be 5.57 and 0.86, respectively. From this result, Clostridium thermosaccharyliticum was chosen to be the reference organism to establish the adequate thermal process schedule. The chosen formulation was used to establish a thermal process for the product. The processing time of 90 minutes at 250°F was found to be adequate. Cut-out tests showed the product to be commercially-sterile.